Eschweilera podoaquilae: A new species of Lecythidaceae from northwestern Ecuador - Cornejo, Xavier (Phytotaxa, 2023)
Eschweilera Mart. ex DC. s.l. (1828: 293), a neotropical genus of Lecythidaceae reportedly as ¨taxonomically difficult…¨, comprises ca. 100 species of often tall trees (Mori & Prance 1990, Mori et al. 2017), which is centered in the Guayana floristic region (Guiana Shield + north-central Amazon; Vargas & Dick 2020) in tropical South America, and it is distributed from Veracruz in Mexico to southern Brazil (Mori et al. 1990, 2015, 2017). Nineteen species of Eschweilera have been recorded for Ecuador from sea level up to 3.000 m, in moist to pluvial forests, and several species have not been formally described (Jørgensen & León 1999, Mori & Cornejo 2011), mainly because the insufficient herbarium material or inadequate collections. During herbarium and fieldwork carried out to document species of Lecythidaceae for the Flora of Ecuador (Cornejo & Mori, in prep.), a new species that belongs to the monophyletic Eschweilera integrifolia clade (Mori et al. 2017) has been found. Characters common to species of this clade include an androecial hood with three to four coils, style thick and very short or sometimes absent, and the geographic distribution on the Pacific slope of the Andes. This taxonomic novelty has been studied in the field by the author in two localities of northwestern Ecuador, and it is formally presented here.